A CORRELATION BETWEEN SIMPLE PAST TENSE MASTERY AND WRITING NARRATIVE TEXT MASTERY - Siti Meutia Sari (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2020)
The aims of this research are to find out: 1) The extent of the students’ mastery in simple past tense at the eleventh grade of SMA Negeri 2 Padangsidimpuan, 2) The extent of the students’ mastery in writing narrative text mastery at the eleventh grade of SMA Negeri 2 Padangsidimpuan, 3) Whether there a significant correlation between simple past tense mastery and writing narrative text mastery at the eleventh grade of SMA Negeri 2 Padangsidimpuan. In order to get the aims of this research is all of the eleventh grade students of SMA Negeri 2 Padangsidimpuan in the period of 2018 / 2019. The sample is taken from the population by random sampling consists of 44 students. This study is carried on by using descriptive method. Furthermore, the instrument is used for collecting the data by giving test to the students. After the data is gotten from the field of the research, the data will be analyzed by descriptive and statistic analysis, by using the formulation “ r “ Product Moment. It can be concluded that the simple past tense of students is categorized “ enough “ ( 64,09 ) and narrative text of students is categorized “ good “ ( 71,13 ). After the data had been gained from the field of the research, the data was analyzed, the writer got rxy = 0,957 and rtable is 0,304 at the 5 % significant level, rxy is greater then rtable. It means that the hypothesis is accepted.